Self-reported healthcare waste segregation practice and its correlate among healthcare workers in hospitals of Southeast Ethiopia - Biniyam Sahiledengle (BMC, 2019)
Abstract Background The key to the effective management of healthcare wastes is segregation of the waste at the point of generation; no matter what final strategy for treatment and disposal of wastes is selected, it is critical that waste streams are separated. In Ethiopia, healthcare waste segregation practice among healthcare workers is overlooked and scarcely addressed in the scientific literature. This hospital-based cross-sectional study was, therefore, conducted to assess healthcare waste segregation practice and its correlate among healthcare workers in Bale zone, southeast Ethiopia. Methods All five hospitals found in Bale zone were included and the study participants were selected using a systematic sampling technique from each hospital. Data were collected through interview using structured questionnaires. Descriptive statistics were computed. Bivariate and multivariable logistic regression analyses were employed to identify factors that correlate with healthcare waste segregation practice. Results A total of four hundred and nine healthcare workers participated in the study, for a response rate of 97.4%. Of these, 220(53.8%) (95% CI: 49.1-58.9) of healthcare workers were found to have reported good healthcare waste segregation practice. Being male gender (AOR = 1.70, 95%CI: 1.04-2.78), less than 30 years of age (AOR = 2.02, 95%CI: 1.06-3.84), less than 2 years work experience (AOR = 2.95, 95%CI: 1.39-6.26), having good self-reported standard precaution practice (AOR = 8.47,95%CI:4.98-14.42), and working in a department with an on-site healthcare waste segregation container (AOR = 2.10, 95%CI:1.24-3.55) were factors that correlated with self-reported healthcare waste segregation practice. Conclusion Overall, only half of the healthcare workers had good healthcare waste segregation practice, which is low and unsatisfactory. Less service year, having good standard precaution practice, and the presence of onsite waste segregation container were the most important variables that correlate with self-reported healthcare waste segregation practice. Therefore, to improve healthcare waste segregation practice health authorities should focus on sufficient allocation of onsite waste receptacles. In addition, periodic training on standard precaution will improve compliance with segregation practice.